História das multiplicidades travestis em muriel total, de laerte coutinho: cartografias discursivas da estética de si por um devir transgênero - Nóbrega Filho, Emanoel Raiff Gomes da (2016)
This thesis discusses the emerging of new types of transvestites subjectivities and new ways of existence called transvestility. With views to that, we have analyzed a series of statements composed of the strip cartoons from the narrative ‘Muriel Total’ by the renowned transgender cartoonist Laerte Coutinho, in which it is possible to observe the transformation of the character Hugo into Muriel. These discourse analysis seek to demonstrate how heteronormativity makes it possible the transvestilities by not allowing their existence, taking into consideration that the same law segregates and produces them. Therefore, according to Butler (2012; 2013) we propose that the abject bodies – the ones which are not allowed by heteronormativity – are discursively produced following desires that can be formed discursively by the norm, deviating from it while they rearrange themselves, resisting to it by not repressing themselves, thus, making transgender ontologies possible. For that purpose, it was also sought to design a panorama, an archaeology of contemporary transvestites, seeking to distinguish them from their predecessors, the hermaphrodite and the transvested individuals – whether considering what was clinically defined as fetishistic transvestitism or by the association with the image of an effeminate man from final 19th century and part of the 20th century. It was also observed on Foucault’s studies of sexuality (2007a; 2007b; 2007c), that the confession – being a tactic used by the Church and by science, especially the psi ones – having being the means to construct sexuality, figures as a trace of a statement of themselves made by transvestites when they start considering themselves as an object of ethical importance. However, due to the main scope of the study, it is criticized the heteronormatizing model of Freudian psychoanalysis that is Oedipus Complex, as long as it is obeserved the productive characteristic of the transgender schizo. Therefore, the research is developed through the analysis of the cartoon stripes, based on the concepts introduced by the French Discourse Analysis, such as, discourse, enouncement, discursive formation, cultural formation and discursive memory, as well as dialoguing with Gender Studies and Anthropology via authors such as Geertz (2008) and Wagner (2012), when discussing about culture, and to philosophy following Foucault’s (2003; 2007a; 2010a), Deleuze and Guattari’s (2010) criticism to psychoanalysis’s modus operandi concerning to the question of power in the relation of desire with the subject and among subjects, implying on a criticism to the (hetero)normative model which, through Oedipus Complex, leads the individual to conceive itself as a heterosexual. Thus, the transvestites’s existence is possible exactly because they do not submit their desire to the obligation of mattering their bodies according to a binary perspective, in which, each gender would be dialectically conceived (masculine/feminine) and performed by the attribution of its respective birth sex, also having their desire oriented to the opposite sex, making the subjects compulsorily heterosexuals. Meanwhile, it is by non-subjecting to the norm, from a force (Thûmos) discursively converted into desire, that transvestites matter their bodies in their abjection, inventing themselves and their culture, new desires, inventing ways of life on the ethical relation with themselves and with others. Thus, leading us to believe that their very existences are etopoietic, for being thumopoietic – thence thumopolitic – whose complexity is bigger than the on powerful relation of desire with the regular individual, once it is by abjection that the transvestites claim their ontological status, their existence becoming different transgender beings.